History and future perspectives of adipose tissue macrophage biology - Kado, Tomonobu; Nishimura, Ayumi; Tobe, Kazuyuki (Frontiers in Pharmacology, 2024)
Macrophages contribute to adipose tissue homeostasis; however, they are also thought to be responsible for insulin resistance in obesity. Macrophages, which were oversimplified in past methodologies, have become rather difficult to understand comprehensively as recent developments in research methodology have revealed their diversity. This review highlights recent studies on adipose tissue macrophages, identifies controversial issues that need to be resolved and proposes a scenario for further development of adipose tissue macrophage biology.